Conditioning Factors in Learning Vocal Jazz in Argentina. (Revista Argentina de Musicología, 2018)
In recent years, different scientific branches have echoed the study of voice function within the singing activity and different disciplines have expanded our knowledge of it. However, despite the growing research on music education, in what relates specifically to vocal learning there is still a limited knowledge of the factors involved in the training of the singers and all the practices adopted by them. The aim of this paper is to analyze the parameters that condition the learning of vocal jazz. For this purpose, a series of semi-structured interviews with singers with broad experience in the current jazz scene in Argentina have been conducted. The information obtained has been analyzed taking into consideration research focussed on various aspects of the singing voice and learning of popular music, with special emphasis on jazz.
Keywords: vocal jazz; Argentina; singer; training; learning